Expression and Localization of Cathepsins B, D and G in Cancer Stem Cells in Liver Metastasis From Colon Adenocarcinoma - Mehrotra, Shreeja; Wickremesekera, Susrutha K.; Brasch, Helen D.; Van Schaijik, Bede; Marsh, Reginald W.; Tan, Swee T.; Itinteang, Tinte (Frontiers in Surgery, 2018)
Aim: We have previously identified and characterized cancer stem cell (CSC) subpopulations in liver metastasis from colon adenocarcinoma (LMCA). In this study we investigated the expression and localization of cathepsins B, D and G, in relation to these CSCs. Methods: 3,3-Diaminobenzidine (DAB) immunohistochemical (IHC) staining for cathepsins B, D and G was performed on 4μm-thick formalin-fixed paraffin-embedded LMCA sections from nine patients. Immunofluorescence (IF) IHC staining was performed on three representative samples of LMCA from the original cohort of nine patients, to determine the localization of these cathepsins in relation to the CSC subpopulations. NanoString mRNA analysis and Western Blotting (WB) were used to examine the transcript and protein expression of these cathepsins, respectively. Enzyme activity assays were utilized to determine their functional activity. Data acquired from counting of cells staining positively of the cathepsins on the DAB IHC-stained slides and from Nanostring mRNA analysis were subjected to statistical analyses to determine significance. Results: DAB IHC staining demonstrated expression of cathepsins B, D and G within LMCA. IF IHC staining demonstrated the expression of both cathepsin B and cathepsin D by the OCT4- cells within the tumor nests and the OCT4+ CSC subpopulation within the peritumoral stroma. NanoString mRNA analysis showed significantly greater transcript expression of cathepsin B and cathepsin D, compared to cathepsin G. WB confirmed expression of cathepsin B and cathepsin D proteins, while cathepsin G was below detectable levels. Enzyme activity assays showed functional activity of cathepsin B and cathepsin D. Conclusion: Our study demonstrated the novel finding of the expression of cathepsin B, cathepsin D, and possibly cathepsin G by the putative CSC subpopulations within LMCA.